(untitled) (Revista Nacional de Odontología, 2017)
Introduction: The use of Low-level Laser Therapy (Low-level Laser Therapy, lllt ) has brought with it the evolution of anti-inflammatory, analgesic and pro-healing treatments due to cell photostimulation on the mitochondria; this increases the generation of energy (atp), which accelerates blood microcircula- tion and produces changes in the hydrostatic pressure of the capillary. Case presentation: A 25-year-old patient who attended the oral surgery service at the dental clinics of a university for the extraction of retained lower third molars. Upon radiographic examination, asympto- matic tooth 48 was observed in mesioangular position according to Winter’s classification and class b ii according to Pell & Gregory’s classification. Materials and methods: The patient received post-exodontia treatment with Low-level Laser Therapy. Results: The effect achieved with the application of lllt in the case resulted in pain control at 48 hours, anti-inflammatory effect on the third day and evident tissue regeneration on the seventh day. Conclusions: Low-level Laser Therapy could be an alternative post-surgical control of retained third molar extractions that would prevent the administration of anti-inflammatory and analgesic drugs in some cases.